Analytic number theory, modular forms and q-Hypergeometric series : in honor of Krishna Alladi's 60th birthday, University of Florida, Gainesville, March 2016 /: in honor of Krishna Alladi's 60th birthday, University of Florida, Gainesville, March 2016. (2017) - Unknown
No abstract available